29‐Plex tandem mass tag mass spectrometry enabling accurate quantification by interference correction. Issue 19 (27th June 2022) - Sun, Huan; Poudel, Suresh; Vanderwall, David; Lee, Dong Geun; Li, Yuxin; Peng, Junmin
Abstract: Tandem mass tag (TMT) mass spectrometry is a mainstream isobaric chemical labeling strategy for profiling proteomes. Here we present a 29‐plex TMT method to combine the 11‐plex and 18‐plex labeling strategies. The 29‐plex method was examined with a pooled sample composed of 1×, 3×, and 10× Escherichia coli peptides with 100× human background peptides, which generated two E. coli datasets (TMT11 and TMT18), displaying the distorted ratios of 1.0:1.7:4.2 and 1.0:1.8:4.9, respectively. This ratio compression from the expected 1:3:10 ratios was caused by co‐isolated TMT‐labeled ions (i.e., noise). Interestingly, the mixture of two TMT sets produced MS/MS spectra with unique features for the noise detection: (i) in TMT11‐labeled spectra, TMT18‐specific reporter ions (e.g., 135N) were shown as the noise; (ii) in TMT18‐labeled spectra, the TMT11/TMT18‐shared reporter ions (e.g., 131C) typically exhibited higher intensities than TMT18‐specific reporter ions, due to contaminated TMT11‐labeled ions in these shared channels. We further estimated the noise levels contributed by both TMT11‐ and TMT18‐labeled peptides, and corrected reporter ion intensities in every spectrum. Finally, the anticipated 1:3:10 ratios were largely restored. This strategy was also validated using another 29‐plex sample with 1:5 ratios. Thus the 29‐plex method expands the TMT throughput and enhances the quantitative accuracy.